Evaluation of an Incentive Program on Educational Achievement of Indigenous Students1. Issue 298 (9th June 2016) - Dulleck, Uwe; Silva‐Goncalves, Juliana; Torgler, Benno
Abstract : This article introduces an incentive program that attempts to close the gap in educational attainment between Indigenous and non‐Indigenous Australians, and provides an evaluation of its effectiveness. The program uses in‐kind incentives conditional on achievement of a specific target for academic grades, classroom behaviour and attendance, coupled with information sessions on the importance of educational achievement. In 2012, all indigenous students enrolled in 21 high schools in Queensland were invited to take part in the program. Using a differences‐in‐differences design, we find that the program improved classroom behaviour and academic grades and reduced unexplained absences for female students only. In contrast, the program improved scores on a standardised national assessment test for male students. Moreover, we find that the program is only effective for students from intact families.